2001
DOI: 10.1088/0741-3335/44/1/201
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical processes in complex plasmas

Abstract: In this review, a systematic overview of dynamical processes in complex (dusty) plasmas is given. Complex plasmas consist of electrons, ions, neutrals, and microparticles of nanometre to micrometre size, which are responsible for the unusual properties of this kind of plasmas, such as the formation of liquid or solid phases at strong electrostatic coupling. The examples represent the progress in this field within the last five years and mostly such cases were chosen, in which experimental results could be comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(97 citation statements)
references
References 210 publications
3
94
0
Order By: Relevance
“…The interactions between dust particles and warm plasmas represent a variety of often very complicated problems, where not all questions are amenable for theoretical or analytical studies, not even when individual dust particles are considered (Piel and Melzer, 2002;Fortov et al, 2005). In the present work we analyze the charging of a single dust particle by numerical methods.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between dust particles and warm plasmas represent a variety of often very complicated problems, where not all questions are amenable for theoretical or analytical studies, not even when individual dust particles are considered (Piel and Melzer, 2002;Fortov et al, 2005). In the present work we analyze the charging of a single dust particle by numerical methods.…”
Section: Introductionmentioning
confidence: 99%
“…7. The potential barrier for moving a particle inwards from (27,4) to (26,5) [lowest curve] shows where the particle returns; interestingly the sharp increase at r 0 ≈ 0.85 is matching the return point of r = 0.39mm in the experiment, cf. Fig.…”
Section: Structural Transitions In the Experimentsmentioning
confidence: 68%
“…∆ E/N config. 3.030266 (27, 4) 0.000479 (26,5) 0.000006 (27,4) Table 1 Energy difference between metastable states and the ground state (the ground state and its energy is given by bold numbers) as seen in Fig. 3.…”
Section: Ground and Metastable Statesmentioning
confidence: 99%
“…We also neglect wake field induced attraction (Melzer et al 2000b;Hebner et al 2003;Hebner and Riley 2004) found in the sheath region and the effect of non-uniform sheath electric field on the dust grains (Melzer et al 1994;Piel and Melzer 2002). We use single mass and single size grains under uniform gravity condition.…”
Section: Governing Equationsmentioning
confidence: 99%